W9 Making best use of the standards in practice. (5th November 2017) - Purva, M; Nicklin, J; Howes, S; Bohnert, C; Gosai, J
Abstract : The workshop provides an opportunity for the simulation community to examine the ASPiH accreditation process. The ASPiH accreditation badge assures healthcare professionals, educators, regulators and patients that a high quality of simulation-based education, mapped to the ASPiH standards is provided by the organisation or provider who holds the badge. During this workshop participants will engage in small group exercises, contextualising and reviewing the ASPiH accreditation documents. Support and advice will be provided for those intending to or undertaking the ASPiH accreditation process. Objectives: Explore the role of ASPIH standards and accreditation in promoting good practice Discuss the utility and relevance of the ASPIH accreditation process Review the complementary roles of other standards: ASPE standards with ASPiH standards Programme: 1430–1435 Introduction 1435–1440 ASPiH standards and accreditation-putting into practice 1440–1455 Small groups exercises with provided documents 1455–1510 Feedback from groups 1510–1520 Complementing ASPiH with ASPE 1520–1530 Feedback and close Materials needed: 1. Copies of the ASPiH standards 2. Copies of the guidance document 3. Copies of the 3 types of accreditation forms 4. Consultation survey questions pertaining to individual, programme and organisational-each printed on a separate sheet-this will be distributed to each group that they will complete during the 15 minutes allocated to them. 5. Power point slide of the ASPIh standards -just one slide we can have this as a backdrop.